Young Thomas More and the arts of liberty - Wegemer, Gerard B. (Cambridge University Press, 2011)
"This book analyzes Thomas More's earliest thoughts on the statecraft needed to enhance liberty and peace in a culture favoring war. It includes a close study of his little-known works - his poetry, letters, Lucian translations, declamation on tyrannicide, coronation ode for Henry VIII, and life of Pico della Mirandola - as well as Richard III and Utopia"--